CRITERIA AND INDICATORS OF EFFECTIVE INVESTMENT - Solieva Umida Alisher qizi (Innovate Conferences, 2025)
Effective investment plays a key role in the economic development of any country. In the modern world, it is especially important to choose investment projects correctly and evaluate their profitability in order to maximize profits and minimize risks. Knowing the main criteria and indicators of investment efficiency helps investors make informed decisions and achieve success.